Manajemen Risiko, Keselamatan, dan Kesehatan Kerja pada Pengelolaan Limbah Aluminium di PT. Buan Mukim Mandiri - Maulidiya, Nur; Heidar, Muhammad; Nurhalizah, Yunita; Kusuma, Muhammad Rizki; Ishak, Burhanish Sultan; Wiwin, Wiwin; Rani, Dhita Puspita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The aluminum waste management industry has a high level of occupational risk due to exposure to metal dust, extreme temperatures, and the potential for workplace accidents from smelting and processing activities. This study aims to analyze the implementation of risk management and occupational safety and health (OHS) systems in aluminum waste management at PT. Buan Mukim Mandiri. The study used a descriptive qualitative approach with data collection techniques in the form of in-depth interviews with purposively selected informants, including OHS/EHS officers, related staff, and operational workers. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing, with data validity maintained through source triangulation. The results of the study indicate that the company has implemented systematic risk management through hazard identification, preparation of Job Safety Analysis, provision of personal protective equipment, technical controls, and implementation of OHS training and periodic health checks. The main risks faced by workers include exposure to aluminum dust, heat, and the potential for workplace accidents. Although the OHS system has been running quite well, obstacles are still found in the form of a lack of consistency in the use of PPE, differences in levels of safety awareness, and the need to strengthen the OHS culture. This study recommends increased supervision, risk-based technical controls, more specific health programs, and more applicable and sustainable K3 training.